Towards a portfolio of FLOSS project success measures - Kevin Crowston; Annabi, Hala; James Howison; Masango, Chengetai (Workshop on Open Source Software Engineering, 26th International Conference on Software Engineering, 2004)
Project success is one of the most widely used dependent variables in information systems research. However, conventional measures of project success are difficult to apply to Free/Libre Open Source Software projects. In this paper, we present an analysis of four measures of success applied to SourceForge projects: number of members of the extended development community, project activity, bug fixing time and number of downloads. We argue that these four measures provide different insights into the collaboration and control mechanisms of the projects.